A case of lateral calcaneal neuropathy: Lateral heel pain. Issue 4 (24th August 2016) - Kim, Ki Hoon; Park, Byung Kyu; Kim, Dong Hwee
ABSTRACT: Introduction : Although isolated injury of the sural nerve is frequently reported, entrapment involving the lateral calcaneal branch of the sural nerve (LCSN) is very rare. Methods : We report the case of a 29‐year‐old man with lateral calcaneal neuropathy of the sural nerve without any history of trauma. The diagnosis was based on clinical, electrophysiologic, and radiologic studies, including ultrasonography (US) and MRI. Results : US revealed a spindle‐shaped swelling in the posterior part of the sural nerve around the lateral malleolus. MRI showed a small lesion in the sural nerve close to the lesser saphenous vein around the level of the lateral malleolus. Two months after conservative management, the numbness and tingling in the lateral calcaneal region improved. Conclusions : Entrapment of the LCSN can arise from tight shoes. US is useful for evaluating the cutaneous nerve lesions that may be too small to detect by MRI. Muscle Nerve 54 : 801–804, 2016